Facilitating trade through regulatory cooperation : the case of the WTO's TBT/SPS Agreements and Committees (World Trade Organization GenevaCH, 2019)
This publication highlights how the WTO's Agreements on Technical Barriers to Trade (TBT) and on the Application of Sanitary and Phytosanitary Measures (SPS) and the work of their related Committees promote opportunities for regulatory cooperation among governments and ease trade frictions. The study also makes recommendations on how to benefit further from the transparency and cooperation opportunities provided by the TBT and SPS Agreements.